Cultural Representation and Desire in Junichiro Tanizaki’s Diary of a Mad Old Man: Mimetic Criticism - Fibria Cahyani; Dyah Nugraheny Priastuti (Wanastra: Jurnal Bahasa dan Sastra, 2026)
This study examines the representation of Japanese cultural-historical values not only as a reflection of social reality but also as a selective strategy for interpreting cultural tradition and the aging process in Junichiro Tanizaki’s Diary of a Mad Old Man through the lens of mimetic criticism. Employing a descriptive qualitative method with contextual analysis, the primary data consist of written documents from the novel; secondary data include relevant books and journal articles. These findings expose tensions between cultural tradition and individual desire, manifested in: (1) Kabuki and Agemaki are symbol of aesthetic obsession; (2) Geisha is firmly as a legitimizing structure of patriarchy, desire, and masculinity; (3) Kimono depicts as an expression of the tradition materiality; and (4) Seasonal festivals are the representation of cultural transition between traditional Japanese values and postwar modernity. These findings show that the author uses elements of cultural tradition to express Japan’s social and cultural reality through his character’s life experiences. Consequently, this study offers insights into literary and cultural studies by exploring how mimetic representation relates to cultural tradition, material practices, and individual desire in Tanizaki’s depiction of postwar Japanese society.